Exploration Of Ethnomathematics In The Museum Wayang and Artifact Purbalingga As A Medium of Mathematics Learning - Azzah Inayatul; Muhammad 'Azmi Nuha; Samuel John Parreño (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This research is based on students who think that math is a difficult and boring subject. Learning math is just something that complicates life without seeing the relevance to the real world, so they lose interest. This has an impact on low learning outcomes, developing a negative attitude towards learning. Therefore, there is a need for new innovations to support learning, so as to increase student attractiveness. This research focuses on identifying the analysis of mathematical concepts in the Museum Wayang and Artifact Purbalingga. This research uses descriptive qualitative research with an ethnographic approach. Where the data findings come from the results of documentation, observation, and interviews. Data analysis techniques carried out using Spradley's data analysis techniques, namely domain analysis, taxonomy, componential, and cultural themes. Domain analysis found the domains of objects, tools, animals, and motifs. Taxonomy analysis in the form of a concept map, componential analysis in the form of a review of each component. Analysis of cultural themes found seven sub-themes namely flat buildings, space buildings, symmetry and congruence, sets, permutations, number patterns and reflections. The results of this study indicate the existence of mathematical concepts in the Museum Wayang and Artifact Purbalingga, namely, the concept of flat shapes, spaces, congruence, sets, permutations, number patterns and reflections found in the collection of wayang and artifacts.